Wallace & Gromit : The Curse of the Were-Rabbit & Gromit's Tail-Waggin' DVD - 1939-2021; Sallis, Peter; Fiennes, Ralph; Bonham Carter, Helena; Kay, Peter; 1973-; Smith, Nicholas; 1934-2015; Baker, Bob; 1966-; 1960-; Shelley, Carla; et al. (Dreamworks Animation, 2006)
Vege-mania is sweeping Wallace and Gromits neighborhood, so the two enterprising chums are cashing in with their company, "Anti-Pesto." Business is booming, and only days remain before the annual Giant Vegetable Competition. Suddenly, a huge, mysterious, veg-ravaging "beast" begins attacking the towns vegetable plots at night, and the competition hostess, Lady Companula Tottington, commissions Anti-Pesto to catch it and save the day.
Keywords: Wallace; (Fictitious character); Drama; Gromit; (Fictitious character); Drama; Drama; Contests; Control; Pests; Drama; Animated films; Clay animation films; Comedy films; Drama; Feature films; Fiction films; Video recordings for the hearing impaired; Drama; Video recordings for the hearing impaired; Juvenile works; Childrens films; Feature films; Clay animation films; Films for the hearing impaired; Fiction films; Childrens films; Comedy films; Animated films